Clinical value of miR-200b in diagnosis and prognosis of childhood pneumonia - Weiwei Qi; Beibei Teng; Fan Zhang; Ying Chen; Jinmei Xu; Jinling Luan (BMC Pediatrics)
Abstract Background Childhood pneumonia (CP) is a common respiratory infectious disease in children with high morbidity and mortality. However, differential changes in miRNAs may interact with the regulation of CP. The aim of this paper was to discuss the miR-200b expression in CP and its diagnostic and prognostic value. Methods RT-qPCR was used to measure the miR-200b expression in venous blood. ROC curve was adopted to assess the diagnostic ability of miR-200b in children with CP. Logistic analysis was adopted to study the risk factors are related to CP. Kaplan-Meier was employed to analyze the prognostic ability of miR-200b in CP. Transfection of MRC-5 cells in vitro was used to verify the impact of miR-200b on cell proliferation and apoptosis. Results The expression of miR-200b in serum of CP children was upregulated. ROC analysis prompted that upregulation of miR-200b could be effective in distinguishing between CP and healthy children. Compared with the good prognosis group, miR-200b expression was elevated in the poor prognosis group. Kaplan-Meier reminded that high expression of miR-200b led to a poor prognosis in CP. Cells experiments demonstrated that transfection with miR-200b inhibitor encouraged cell proliferation and inhibited apoptosis, whereas transfection with miR-200b mimic had the contrary result. Conclusions miR-200b had high diagnostic and prognostic value for children with CP and may become a biomarker for clinical diagnosis and prognosis. Clinical trial number Not applicable.